2008
DOI: 10.1111/j.1462-5822.2008.01193.x
|View full text |Cite
|
Sign up to set email alerts
|

The two homologous chaperonin 60 proteins ofMycobacterium tuberculosishave distinct effects on monocyte differentiation into osteoclasts

Abstract: SummaryMycobacterium tuberculosis produces two homologous chaperonin (Cpn)60 proteins, Cpn60.1 and Cpn60.2 (Hsp65). Both proteins stimulate human and murine monocyte cytokine synthesis but, unlike Cpn60 proteins from other microbial species, fail to stimulate the breakdown of cultured murine bone. Here, we have examined the mechanism of action of these proteins on bone remodelling and osteoclastogenesis, induced in vitro in murine calvarial explants and the murine monocyte cell line RAW264.7. Additionally, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 49 publications
0
30
0
Order By: Relevance
“…This raised the question as to whether the Mtb Hsp60 proteins could inhibit bone resorption. Although the two Mtb Hsp60 proteins share over 60% sequence identity, the Hsp60.2 protein has no influence on the process of osteoclast formation, while the Hsp60.1 protein turns out to be a potent inhibitor of murine osteoclast formation both in vitro and in vivo (Winrow et al 2008). The process of osteoclast formation is multistaged and takes up to 7 days.…”
Section: Hsp60mentioning
confidence: 99%
See 1 more Smart Citation
“…This raised the question as to whether the Mtb Hsp60 proteins could inhibit bone resorption. Although the two Mtb Hsp60 proteins share over 60% sequence identity, the Hsp60.2 protein has no influence on the process of osteoclast formation, while the Hsp60.1 protein turns out to be a potent inhibitor of murine osteoclast formation both in vitro and in vivo (Winrow et al 2008). The process of osteoclast formation is multistaged and takes up to 7 days.…”
Section: Hsp60mentioning
confidence: 99%
“…The process of osteoclast formation is multistaged and takes up to 7 days. It has been found that Mtb Hsp60.1 can block osteoclast formation in vitro even after the process has been going for 4 days (Winrow et al 2008). A partial explanation for the inhibitory effect of Mtb Hsp60.1 is that it inhibits the transcription of a key osteoclast transcription factor, nuclear factor of activated T cells (NFATc1).…”
Section: Hsp60mentioning
confidence: 99%
“…This possibly flies in the face of the evidence that 'Hsp70' is a pro-inflammatory factor. This was the situation with Hsp60 until more recent studies, described above, revealed that the human and M. tuberculosis Hsp60.1 proteins can inhibit leukocyte activation [see 29,69]. Thus it is possible that Hsp70…”
Section: Hsp70 Familymentioning
confidence: 98%
“…Moreover both proteins differ markedly in their ability to modulate the formation of the major cell population, the osteoclast, which is responsible for homeostatic bone resorption. Thus the chaperonin 60.1 protein is a potent inhibitor of osteoclast formation while the chaperonin 60.2 protein neither promotes nor inhibits osteoclastogenesis [29].…”
Section: Molecular Chaperone Sequence Conservation and Biological Funmentioning
confidence: 98%
See 1 more Smart Citation